2023
DOI: 10.3390/foods12142654
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Stability and Bioaccessibility of Carotenoid and Carotenoid Esters from a Papaya By-Product Using O/W Emulsions

Sara Lara-Abia,
Gloria Lobo,
Noelia Pérez-Pascual
et al.

Abstract: The aim of the present work was to improve the stability and bioaccessibility of carotenoids from green oil extracts obtained from papaya by-products using oil-in-water (O/W) emulsions. The effects of different concentrations of pectin (1%, 2%, and 3%), a high-molecular-size emulsifier, together with Tween 20, a low-molecular-size emulsifier, high-speed homogenization conditions (time: 2, 3, 4, and 5 min; rpm: 9500, 12,000, 14,000, and 16,000 rpm), and high-pressure homogenization (HPH) (100 MPa for five cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The gastrointestinal conditions such as pH and enzyme content can react with phenolic compounds causing a decrease associated with the isomerization and hydrolysis of the compounds [14]. Oil-water emulsions used in the protection of fat-soluble extracts have better bioavailability due to the high solubility of these compounds [53]. Boyraci et al [54] reported a decrease from 91 to 87% of phenolic compounds in propolis extracts during gastrointestinal digestion.…”
Section: Total Phenolsmentioning
confidence: 99%
“…The gastrointestinal conditions such as pH and enzyme content can react with phenolic compounds causing a decrease associated with the isomerization and hydrolysis of the compounds [14]. Oil-water emulsions used in the protection of fat-soluble extracts have better bioavailability due to the high solubility of these compounds [53]. Boyraci et al [54] reported a decrease from 91 to 87% of phenolic compounds in propolis extracts during gastrointestinal digestion.…”
Section: Total Phenolsmentioning
confidence: 99%